2016
DOI: 10.2139/ssrn.2887931
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Central Bank Independence

Abstract: This paper reviews recent research on the political economy of monetary policy-making, both by economists and political scientists. The traditional argument for central bank independence (CBI) is based on the desire to counter inflationary biases. However, studies in political science on the determinants of central bank independence suggest that governments may choose to delegate monetary policy in order to detach it from political debates and power struggles. This argument would be especially valid in countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Building on this expansion during the global financial crisis, central bank actions in response to the COVID-19 pandemic have been unprecedented in history in terms of speed, scope, and scale. 4 Observers of central banks have raised questions about the rapid expansion of new instruments and unconventional monetary policies and the implications of these for central bank independence (De Haan and Eijffinger 2016).…”
Section: Legal Frameworkmentioning
confidence: 99%
“…Building on this expansion during the global financial crisis, central bank actions in response to the COVID-19 pandemic have been unprecedented in history in terms of speed, scope, and scale. 4 Observers of central banks have raised questions about the rapid expansion of new instruments and unconventional monetary policies and the implications of these for central bank independence (De Haan and Eijffinger 2016).…”
Section: Legal Frameworkmentioning
confidence: 99%
“…The scale of central bankers' influence varies between the countries and governors' terms -it is usually dependent on the personal characteristics of the governors [Adolph, 2013]. Still, these ties are becoming especially important in the era of large-scale purchases [Fernández-Albertos, 2015;De Haan, Eijffinger, 2016]. Political authorities are more tempted to pursue expansive policies given that the share of sovereign debt is backed by the central banks.…”
Section: Sum Of Deviationsmentioning
confidence: 99%
“…Researchers such as de Haan and Eijffinger (2016) observed that the last global financial market crisis of 2007/2008 has altered the perceived role of central banks and that this can be seen in massive use of new unconventional monetary and macro-prudential policy measures; though financial stability and unconventional policy moves of the monetary authority have a much more impactful distributional consequences than conventional monetary policies as well as potential implications for the independence of the central bank. It can be seen that Central banks' policies may have serious impact on workers and capitalists, debtors and creditors, finance and industry etc.…”
Section: Distributive Role Of Central Bank Policymentioning
confidence: 99%